Chronic subthreshold cortical stimulation and stimulation-related EEG biomarkers for focal epilepsy. Issue 1 (6th September 2019) - Lundstrom, Brian Nils; Gompel, Jamie Van; Khadjevand, Fatemeh; Worrell, Greg; Stead, Matt
Abstract: Brain stimulation offers an alternative to focal resection for the treatment of focal drug-resistant epilepsy. Chronic subthreshold cortical stimulation is an individualized biomarker-informed open-loop continuous electrical stimulation approach targeting the seizure onset zone and surrounding areas. Before permanent implantation, trial stimulation is performed during invasive monitoring to assess stimulation efficacy as well as to optimize stimulation location and parameters by modifying interictal EEG biomarkers. We present clinical and neurophysiological results from a retrospective analysis of 21 patients, showing a median percent reduction in seizure frequency of 100% and responder rate of 89% with a median follow-up of 27 months. About 40% of patients were free of disabling seizures for a 12-month period or longer. We find that stimulation-induced decreases in delta (1–4 Hz) power and increases in alpha and beta (8–20 Hz) power during trial stimulation correlate with improved long-term clinical outcomes. These results suggest chronic subthreshold cortical stimulation may be an effective alternative approach to treating focal drug-resistant epilepsy and that short-term stimulation-related changes in spectral power may be a useful interictal biomarker and relate to long-term clinical outcome. Abstract : Focal drug-resistant epilepsy remains challenging to treat. Chronic subthreshold cortical stimulation (CSCS) offers a novel individualized treatment approach that targets the seizure onset zone with continuous electrical stimulation. Stimulation-related changes in EEG biomarkers during trial stimulation may help guide implantation of permanent electrodes. Graphical Abstract: